Factors influencing the transfer of training / Muhammad Amin Azhar - Azhar, Muhammad Amin (Faculty of Business and Management, 2019)
In this era, training and development is one key area in which all the organization realised its importance. Major companies with huge budget on the training are able to provide the best training for their employees. However, small to medium companies were not left behind in this matter since they also heavily invested on the training program. With a huge investment on training program, all would come to waste if the transfer of training itself is not achieved successfully. This study will be looking into the factors influencing the transfer of training among the employees of Pertubuhan Keselamatan Sosial (PERKESO) Melaka. The researcher used three different independent variables consisting of supervisor support, peer support and training design which could influence the transfer of training. This study was conducted using simple random method for the sampling size and use the primary data from questionnaire distributed to the respondents. The respondents that were selected are amounted to a total of 53 respondents from PERKESO Melaka. The data then was analysed using Statistical Package for Social Science (SPSS). The results found that supervisor support and peer support were the only independent variable that influence the transfer of training, but training design does not. The findings proved that supervisor support is the most influencing factors in transfer of training among the employees of PERKESO Melaka.